Toxicity Assessment of the Biogenic Amines Cadaverine and Putrescine in Aquatic Organisms - Braga, Ana Paula Andrade [UNESP]; Vallim, José Henrique; Castanha, Rodrigo Fernandes; de Castro, Vera Lucia Scherholz Salgado; Marin-Morales, Maria Aparecida [UNESP] (Springer Nature, 2024)
Cemeteries are among the most polluting sources of groundwater and surface water in the world. Necro-leachate, a liquid released during the putrefaction of corpses, is the main culprit of such pollution. Among the compounds in this liquid are the potentially toxic amines cadaverine and putrescine, which are still poorly understood in terms of the environmental health risks they pose. This study evaluated the acute toxicity of cadaverine and putrescine, using efficient contamination bioindicators of aquatic environments. Danio rerio and Daphnia magna were exposed to both amines individually or in a mixture. Acute toxicity (LC50) was then observed in both organisms after exposure to the amines individually. Cadaverine showed higher lethality for D. magna (LC50 – 9.5 mg. L−1) and D. rerio (LC50—335.5 mg. L−1) than did putrescine (LC50—36.7 mg. L−1 and LC50- 452.6 mg. L−1, respectively). In embryotoxicity tests with D. rerio (hatching rate and malformations), delayed hatching, vertebral column malformations, and pericardial edema were observed after exposure to an amine mixture. However, co-exposure to cadaverine and putrescine was not toxic to D. magna. The results of this study confirmed the efficiency of the bioindicators used to assess contaminants in cemeteries and raised awareness of the toxic potential of cadaveric decomposition by-products.
Keywords: Aquatic Toxicology; Cemetery Contamination; Danio rerio; Daphnia magna; Environmental Risk Assessment